Governance and Labor Market Outcomes in Fragile States: The Impact of Corruption Control on Unemployment Reduction in Somalia - Dirie, Ahmed Nur; Mohamed , Mahad Abdiwali; Mohamud, Abdiaziz Bashir; Nur, Abdirahman Ahemd; Farah, Mohamed Abdisamed (International Journal of Economics and Financial Issues, 2025)
Corruption impedes economic growth, political stability, skill development, and entrepreneurship by diverting resources from critical sectors such as infrastructure, education, and healthcare. It discourages investment and weakens economic institutions. This study examines the impact of corruption control on unemployment reduction in Somalia, a country grappling with prolonged political instability and fragile institutions. Using annual data from 1996 to 2023, the study employs both the Autoregressive Distributed Lag (ARDL) and Fully Modified Least Squares (FMOLS) methodologies to analyze short-run and long-run dynamics. The results indicate that while the coefficient for corruption control (LNCPR) is negative implying that improvements in controlling corruption are associated with reductions in unemployment this relationship is statistically insignificant in the long run but becomes significant in the short run. Similarly, economic growth (LNGDP) significantly reduces unemployment, while government expenditure (LNGEX) and population growth (LNPOP) are associated with rising unemployment. Diagnostic and stability tests affirm the reliability of the model, and FMOLS results corroborate the long-term estimates. The study highlights the urgent need for Somalia to enhance institutional quality, digitalize its economy, and adopt sustainable employment and industrialization strategies to effectively tackle corruption and unemployment. These findings contribute to a deeper understanding of governance-driven labor market challenges in fragile state contexts.